Understanding Islamophobia in Asia: The Cases of Myanmar and Malaysia. Issue 1 (1st October 2017) - Mohamed Nawab Bin Mohamed Osman
Abstract : In June 2013, Alvin Tan, a prominent Malaysian blogger, posted on Facebook a picture of his girlfriend and himself eating bak kut teh (pork) with the caption "Selamat Berbuka Puasa" (Happy Breaking Fast). The duo had described the dish as "wangi, enak, menyelerakan" (fragrant, delicious, appetizing) and also included a "Halal" logo. During the same month, Rohingya Muslims in Myanmar faced one of the community's worst persecution acts, with several hundred people murdered by Buddhist religious zealots inspired by extremist Buddhist monks. These are but some examples of Islamophobia in Asia. Buddhist nationalist groups such as the Bodu Bala Sena in Sri Lanka and the 969 Movement in Myanmar have encouraged the anti-Muslim violence. In India, the rise of the Hindu nationalist movement has seen the forced conversion of Muslims and increased incidences of violence against Muslims. Despite this endemic rise of Islamophobia, there has been little academic research conducted on Islamophobia in Asian countries. This is contrasted by the trends of Islamophobia as a phenomenon being well-documented in the West. The rise in terror attacks within Europe, the refugee crisis on the same continent, and the strengthening of the right-wing nationalist parties has resulted in the rise of Islamophobia in Europe and North America. This article seeks to better understand Islamophobia in the Asian context through the case studies of Myanmar and Malaysia. It argues that Islamophobia in these countries is largely the result of domestic socio-economic and political issues, rather than the international narrative against Islam and Muslims. There are three parts to this article: first, the discourse against Islam in both countries will be examined. Second, the factors that caused the rise of Islamophobia in both Myanmar and Malaysia will be looked at. Historical ethnic tensions, economic gaps between different communities, state-initiated religious persecution and the rise of right-wing religious organizations will be discussed in this regard. This section will postulate the view that Islamophobia can occur within countries such as Malaysia, especially when the minority groups are dominant in the economic sphere. The article will conclude by analyzing whether the manifestation and raison d'être of Islamophobia in Asia is different from the West. The outcome of the inquiry will provide useful analytical tools in studying Islamophobia within the Asian context.